Kontroversi Pembayaran Royalti Atas Hak Cipta Lagu Ahmad Dhani oleh Once Mekel - Rr. Aline Gratika Nugrahani (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2024)
This article aims to examine the articles in Law No. 28 of 2014 concerning Copyright, which was debated by Ahmad Dhani and Once as the basis for arguments regarding royalties. Ahmad Dhani is of the opinion that based on Article 9, Once as a vocalist must pay royalties when performing the songs of the Dewa band he created. Meanwhile, based on Article 23 according to Once, at a music performance, vocalists do not need to ask for permission or license and do not need to pay royalties, because there is an institution that specifically takes care of this, namely LMK (Lembaga Manajemen Kolektif). This article was written using normative research methods with a statutory and case approach. The first part discusses the background to the disagreement between Ahmad Dhani and Once, then it discusses royalties and its problems in Indonesia and the final part examines the accuracy of the articles used by Ahmad Dani and Once as the basis for arguments, so that it is found which articles should be used in resolve licensing and royalty issues. Finally, three conclusions can be drawn, first, the two articles mentioned above can be used as a basis for applying for licenses and collecting royalties for songwriters, only that Article 9 regulates in general that creators are entitled to licenses and royalties, while Article 23 delegates matters regarding licensing and withdrawal of song royalties can be done through LMK. Tulisan ini bertujuan menelaah pasal-pasal pada Undang-undang No. 28 Tahun 2014 Tentang Hak Cipta, yang dipergunakan oleh Ahmad Dhani dan Once sebagai landasan argumentasi terkait lisensi dan royalti hak cipta lagu. Ahmad Dhani berpendapat, Pasal 9 Undang-undang No. 28 Tahun 2014 Tentang Hak Cipta mewajibkan Once sebagai vokalis meminta ijin dan membayar royalti ketika membawakan lagu-lagu grup band Dewa yang diciptakannya. Sedangkan menurut once, berdasarkan Pasal 23 Undang-undang No. 28 Tahun 2014 Tentang Hak Cipta, pada sebuah pagelaran musik, vokalis tidak perlu meminta ijin dan tidak perlu membayar royati, karena telah ada Lembaga yang khusus mengurus hal tersebut yaitu Lembaga Managemen Kolektif. Tulisan ini menggunakan metode penelitian normatif dengan pendekatan perundag-undangan dan kasus. Hingga diperoleh kesimpulan bahwa kedua pasal tersebut di atas dapat dipergunakan sebagai dasar untuk pengajuan lisensi dan menarik royalti bagi pencipta lagu, hanya saja Pasal 9 mengatur secara umum bahwa pencipta berhak atas lisensi dan royalti, sedangkan Pasal 23 mendelegasikan urusan lisensi dan penarikan royalti lagu kepada Lembaga Managemen Kolektif.